Comparing the operations and challenges of pig butchers in rural and peri-urban settings of western Kenya - Levy, M.A.; Dewey, Catherine E.; Poljak, Z.; Weersink, A.; Mutua, Florence K. (Academic Journals, 2014)
The purpose of this cross-sectional, observational study was to describe the pig butcher enterprises in western Kenya; highlighting differences in the operational processes and challenges between rural and peri-urban settings. Fifty pig butchers were interviewed using questionnaires in two districts, Kakamega (peri-urban) and Busia (rural). Results showed that pig butchers were central to the coordination of activities required to connect pig farmers to pork consumers in their communities. Several differences between rural and peri-urban enterprises included use of agents to find pigs, average market weight of pigs, pig prices per kilogram, transport and marketing. Butchers were challenged by credit and capital constraints, seasonality, high pig prices and high search costs. Butchers should be encouraged to have pork inspected and should be included in outreach programs intended to prevent the spread of zoonotic pathogens since they are the last intervention point before pork is consumed. Use of the tape measure for estimating pig weight could help remove inequalities between farmers and butchers abilities to estimate pig weights and could help to reduce search costs for the butcher, thus increasing equity and efficiency of trade between farmers and pig butchers in western Kenya.